Using a semantically enhanced database for business service and process modelling and integration. (1st January 2011) - Galatescu, Alexandra; Greceanu, Taisia; Nicolau, Dragos
The paper motivates and exemplifies a semantic extension of a relational database and the inference on it in a system for the modelling, integration and execution of business services (atomic and local services, executed by companies standing for service providers) and business processes (global services, e.g., processes like procurement or company set-up, dynamically composed of local services). The paper shows how the reference and domain ontologies and also the service and process models based on ontologies have been represented and integrated in a relational database and what kind of inference has been implemented on them. It also shows how the basic features in OWL and OWL-S have been implemented with this semantic extension of the relational database.